2010
DOI: 10.1186/1471-2431-10-61
|View full text |Cite
|
Sign up to set email alerts
|

Early exposure to secondhand tobacco smoke and the development of allergic diseases in 4 year old children in Malmö, Sweden

Abstract: BackgroundEarlier studies have shown an association between secondhand tobacco smoke and allergy development in children. Furthermore, there is an increased risk of developing an allergy if the parents have an allergy. However, there are only few studies investigating the potential synergistic effect of secondhand tobacco smoke and allergic heredity on the development of an allergy.MethodsThe study was population-based cross-sectional with retrospective information on presence of secondhand tobacco smoke durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…First-hand or second-hand exposure to tobacco smoke is a major risk factor for the development of asthma [8,9], while smoking cessation improves asthma symptoms and control [10]. Tobacco smoke has also been shown to be associated with allergic sensitization and sensitization to food allergens [8].…”
Section: Introductionmentioning
confidence: 99%
“…First-hand or second-hand exposure to tobacco smoke is a major risk factor for the development of asthma [8,9], while smoking cessation improves asthma symptoms and control [10]. Tobacco smoke has also been shown to be associated with allergic sensitization and sensitization to food allergens [8].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, there have also been many studies that showed a negative (increased risk) or neutral effect of ETS on allergic sensitization or allergy-related disease. [8][9][10][11] A major concern of all the human studies done to date is that there are differences in other variables (covariates) between children of smoking and non-smoking households, which may lead to a biased estimate of the 'true' effect of ETS. The gold standard for evaluation of the effect of an exposure (tobacco smoke in this case) on an outcome is through a randomized controlled trial (RCT) whereby covariate balance is presumed through the process of randomization.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted in Sweden and Germany have shown that children exposed to tobacco smoke when very young have a higher risk of developing allergic diseases (including atopic eczema) than unexposed children (Kramer et al, 2004;Bohme et al, 2010;Hansen et al, 2010). One of these studies, performed in Sweden on a cohort of children followed until the age of four years, showed that those from families with a history of allergies exposed to second-hand tobacco during their first year of life were much more likely to develop an allergy than children without such a family background exposed to second-hand smoke.…”
Section: Tablementioning
confidence: 99%
“…The most recent studies have tended to show an association between the development of atopic dermatitis in infants and passive exposure to tobacco smoke (Kramer et al, 2004;Bohme et al, 2010;Hansen et al, 2010), although some studies have reported inconclusive results (Ownby and McCullough, 1988;Strachan and Cook, 1998;Hjern et al, 2001;Hancox et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation